Entropy based feature extraction for motorbike engine faults diagnosing using neural network and wavelet transform - Paulraj, Murugesa Pandiyan, Prof. Madya; Sazali, Yaacob, Prof. Dr.; Zin, M.Z.M. (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/